Role of abnormal mitochondrial DNA in Cancer: A review of molecular changes and therapeutic opportunities - Md. Sanower Hossain; Mohammad Touhidul Islam; Md. Abid Hossain; Kajima Rifat; Saila Kabir Maeesa; Mamunur Rahman; Md. Rezaul Islam; Raihana Edros; Sheikh Zahir Raihan; Chrismawan Ardianto; Long Chiau Ming; Bey Hing Goh; et al. (Advances in Redox Research, 2025)
Mitochondria are cellular organelles that play vital roles in a cell's energy production and metabolism. Researchers have made significant progress in understanding mitochondrial dynamics and their effects on human health in recent years. The mitochondrial genome or respiratory chain induces mitochondrial illnesses. Mitochondrial DNA (mtDNA) is a crucial component of mitochondria, and its relationship with cancer has received much attention in recent years. Although there is currently no cure for mitochondrial disorders, various treatment options, such as physiotherapy, hearing aids, pacemakers, and sodium bicarbonate injections, are available for managing symptoms. Diet and exercise can help patients with mitochondrial dysfunction. Individuals with pyruvate dehydrogenase insufficiency benefit from a ketogenic diet and a high-fat, low-carbohydrate diet. Cancer is linked to mitochondrial dynamics, including fusion and fission. These pathways affect cancer stem cell proliferation and recurrence. New cancer therapies may be developed by targeting the proteins involved in mitochondrial fusion and fission. Although some trials have already been conducted, additional research is needed to establish this phenomenon as a full treatment option.